Algebra of Ecology (London Journal of Research In Science: Natural and Formal, 2025)
This monograph examines issues that serve as theoretical prerequisites for constructing an algebra of ecology. These issues include: basic concepts; interactions of ecological factors; a formal definition of the ecological niche; the group-theoretical relationship of survival coefficient functions; and certain representations of the group. It also explores a variety of information models and ecological survival fields.The results of investigating the aforementioned issues provide a basis for the following assertions: Ecological factors are, first, diverse (potentially unlimited) changing natural forces; second, the adaptive responses of biological objects to the impact of ecological factors constitute their survivability; third, the influence of environmental factors on individuals within a population should be considered through the concept of survival functions; fourth, despite the potentially infinite variety of ecological factors, their corresponding survival coefficient functions can be classified into six types. The interaction of environmental factors forms a kind of survivability hypervolume, created by the interaction of survival coefficient functions corresponding to the ecological factors of the environment.
Keywords: PCA; Hordeum vulgar; phenotypic diversity - heat stress index HI; heatmap analysis